Pengembangan Sumber Daya Manusia dalam Manajemen Pendidikan Islam Berbasis Nilai-nilai Qurani - Ilhamsyah, Rizal (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
In Islamic education administration, human resource development (HR) is crucial to building a competent, honorable, and high-quality educational system. Qur'anic values are one strategy that can support human resource development by giving managers, teachers, and students moral guidance and standards. The necessity to match Islamic education management with Qur'anic principles in order to create individuals who are balanced in both intellectual and spiritual dimensions is the basis of this study. The purpose of this study is to examine howthe basis of this study. The purpose of this study is to examine how Qur'anic ideals are used to the development of human resources in Islamic educational institutions and how this affects the standard of education management. The approach involves a review of the literature using a variety of pertinent sources, such as the Qur'an, Islamic education management publications, and scholarly publications that are relevant. According to the study's findings, developing human resources in accordance with Qur'anic principles greatly enhances the moral and academic quality of teachers, school administrators, and students. The Qur'anic values of justice, trust, and cooperation can improve managerial efficacy and foster a more peaceful and fruitful learning environment. This study's contribution is to offer fresh perspectives for the creation of a more comprehensive Islamic education policy that prioritizes moral and spiritual considerations in addition to cognitive ones as the cornerstones of educational administration.